3D-printed carrageenan-based nanocomposites for sustainable resistive sensing devices. (2nd December 2022) - Macedo, Vera M.; Pereira, Nelson; Tubio, Carmen R.; Martins, Pedro; Lanceros-Mendez, Senentxu; Costa, Carlos M.
Abstract: In the scope of natural based materials for sustainable technologies, this work reports on resistive sensors based on carrageenan composites with multi-wall carbon nanotubes (MWCNT). The materials were processed by direct-ink-writing with water as a solvent and mechanical, thermal and electrical property of printed composites have been tailored by varying filler content. It is shown that the inclusion of the carbonaceous fillers does not affect the morphology, polymer phase and the thermal properties of the polymer matrix. On the other hand, the Young modulus increases from 2 to 5 MPa, and the electrical conductivity from 8.3 × 10 −6 up to 0.03 S m −1, with increasing filler content. Graphical abstract: Image 1 Highlights: Carrageenan/multi-wall carbon nanotube composites have been developed by additive manufacturing for resisting sensing applications. Morphology and thermal properties do not depend on filler content. Mechanical, electrical and dielectric properties can be tailored by MWCNT addition. A dc electrical conductivity of 0.03 S m −1 was obtained for the sample with 5 wt% MWCNT content. The suitability of carrageenan-based composites for a new generation of sustainable resistive sensors is demonstrated.